From Fra Angelico to Bonnard: Masterpieces from the Rau Collection - Rau Collection (SKIRA, Italy; Musee de Luxembourg, Paris, 2000)
Exhibition catalog. Jul 2000-Jan 2001.
English
Keywords: N5198-5299 Visual Arts- Private collections and collectors